Developing Nursing Guidelines to Prevent Unplanned Endotracheal Tube Removal in Patients Admitted to Medical Intensive Care Unit - Meksamut, Thitima; Sahmaae, Narisa; Khanbo, Kanokrat; Saelim, Kanjana; Pasor, Arisa; Agasa, Rohana; Naosuwan, Kittiporn; Sahaworapan, Tipsiri (Princess of Naradhiwas University Journal, 2023)
This research and development aimed to study the situation and cause of unplanned extubation tube, to develop nursing guidelines, and to study the effectiveness of nursing guidelines for preventing unplanned extubation tube in patients admitted to the medical intensive care unit, Naradhiwas Rajanagarindra Hospital. This research study was conducted during June-July 2021, consisted of 3 phases: Phase 1, to study the situation and causes of extubation; Phase 2, to develop nursing guidelines; and Phase 3, to evaluate of effectiveness of nursing guidelines to prevent unplanned extubation. There were 30 critically ill patients undergoing oral intubation. The study instruments were unplanned extubation tube risk assessment and nursing guidelines developed from phase 2. A situational study from a 1-year retrospective review of medical records found that the incidence of unplanned extubation tube was 9.54 times per 1,000 intubation days. The cause of the unplanned extubation tube were the level of consciousness changes and the tying of the wrist and endotracheal tube was not standardized. The researcher developed a nursing guideline and the effectiveness of implementing care guideline to prevent unplanned extubation tube. It consisted of 4 items of risk assessment of unplanned extubation tube and 11 items of nursing care. After using the nursing approach to prevent unplanned extubation tube, the incidence was reduced to 4.1 per 1,000 intubation days. Therefore, it is suggested to follow the approach, this helps reduce the incidence of unplanned extubation tube and develop quality of patient care.